Discrimination of bullet types using analysis of lead isotopes deposited in gunshot entry wounds - Wunnapuk K. (2014)
In order to discriminate bullet types used in firearms, of which the victims died, the authors investigated lead isotope ratios in gunshot entry wounds from nine lead (unjacketed) bullets, 15 semi-jacketed bullets, and 14 full-jacketed bullets by inductively coupled plasma-mass spectrometry. It was found that the lead isotope ratio of 207/206 in gunshot entry wounds was the highest with lead bullets, and it decreased in order from fulljacketed to semi-jacketed bullets. Lead isotope ratios of 208/206 or 208/207 to 207/206 at the gunshot entry wound were able to discriminate semi-jacketed bullets from lead and fulljacketed ones, but it was difficult to discriminate between lead and full-jacketed bullets. However, a combination of element and lead isotope ratio analyses in gunshot entry wounds enabled discrimination between lead, semi-jacketed, and full-jacketed bullets. © Humana Press Inc. 2009.